Overexpression of OsF3H modulates WBPH stress by alteration of phenylpropanoid pathway at a transcriptomic and metabolomic level in Oryza sativa - Jan, Rahmatullah; Khan, Muhammad Aqil; Asaf, Sajjad; Lee, In-Jung; Kim, Kyung-Min (Scientific reports, 2020)
The whitebacked planthopper (WBPH), has become a devastating pest for rice crops, causes serious yield losses each year, and urgently needs biological control. Here, we developed a WBPH-resistant rice cultivar by overexpressing the OsF3H gene. A genetic functional analysis of the OsF3H gene confirmed its role in facilitating flavonoid contents and have indicated that the expression of the OsF3H gene is involved in regulation of the downstream genes (OsDFR and OsFLS) of the flavonoid pathway and genes (OsSLR1 and OsWRKY13) involved in other physiological pathways. OxF3H (OsF3H transgenic) plants accumulated significant amounts of the flavonols kaempferol (Kr) and quercetin (Qu) and the anthocyanins delphinidin and cyanidin, compared to the wild type, in response to the stress induced by WBPH. Similarly, OsF3H-related proteins were significantly expressed in OxF3H lines after WBPH infestation. The present study, indicated that the regulation of JA in OxF3H plants was suppressed due the overexpression of the OsF3H gene, which induced the expression of downstream genes related to anthocyanin. Similarly, the OsWRKY13 transcriptional factor was significantly suppressed in OxF3H plants during WBPH infestation. Exogenous application of Kr and Qu increased the survival rates of susceptible TN1 lines in response to WBPH, while decreased the survival rate of first instar WBPHs, indicating that both flavonols exhibit pesticide activity. Phenotypic demonstration also affirms that OxF3H plants show strong resistance to WBPH compared with wild type. Collectively, our result suggested that OsF3H overexpression led to the up-regulation of defense related genes and enhanced rice resistance to WBPH infestation.